2017
DOI: 10.1590/s0100-83582017350100037
|View full text |Cite
|
Sign up to set email alerts
|

AUTOTOXICITY IN TOUGH LOVEGRASS ( Eragrostis plana )

Abstract: ISSN 0100-8358 (print) 1806-9681 (online) AUTOTOXICITY IN TOUGH LOVEGRASS (Eragrostis plana) Autotoxicidade em Capim-annoni (Eragrostis plana)ABSTRACT -Autotoxicity in tough lovegrass has been analyzed in the field, but has never been tested in allelopathy bioassays. Therefore, this study aimed to verify and compare the autotoxicity of leaves and roots from aqueous extracts of tough lovegrass on its germination and early seedling growth. Extracts of green leaves (GL), senescent leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 23 publications
(27 reference statements)
1
14
0
Order By: Relevance
“…These results are similar to those described by Favaretto et al (2015), who detected phenolic compounds only or in higher concentration on leaf extracts, chemical class associated with antimicrobial activity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are similar to those described by Favaretto et al (2015), who detected phenolic compounds only or in higher concentration on leaf extracts, chemical class associated with antimicrobial activity.…”
Section: Discussionsupporting
confidence: 92%
“…Sci., Bom Jesus, v.7, n.4, p.420-427, Out./Dez. 2016 saponins, coumarin, and phenolic acids (caffeic acid, ferulic acid, vanillic, and p-coumaric acid) (Favaretto et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive alien plant species over the past decades have posed serious threats to local biodiversity, ecosystem, environmental quality, which requires confronting this threat and moving towards preventing and eliminating import (Marzialetti, et al 2019;Bartz and Kowarik, 2019), for the rapid and remarkable spread of A. saligna trees in This study was conducted in Al-Jabal Al-Akhdar region, which showed the growth of seeds of these trees can be resisted by using the extracts of their parts, this effect is known as auto-toxicity (Favaretto et al, 2017), and this explains the growth of its seeds at long distances from the mother tree. This result agreed with Richardson et al, (2000) who show that invasive plants spread at long distances from each other, and the results showed that all extracts of golden acacia parts significantly reduced the percentage of germination with a clear increase in the average time of germination, and it was noted that the largest inhibitory percentages were for the flower extract followed by the seeds extract this result was confirmed by ElAyebzakhama et al, (2015) that the greatest inhibitory rates were for A. cyanophyll flower extract on seedlings plants.The high toxicity of the golden acacia flowers may be due to the fact that they contain an abundant amount of phenolic compounds benzoic acid, caffeine, o-coumaric acid, in addition to flavonoids quercetin, naringenin, kaempferol (Al-Huqail et al, 2019), which would It interferes with physiological processes through its effect on cell division and elongation, membrane permeability, ion and water absorption, enzyme synthesis, metabolism, photosynthesis, plant hormone metabolism, respiration, protein and nucleic acid synthesis (Cheng and Cheng, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Decomposed liquid of corn stalk can disturb the metabolism of endogenous hormones in its seedlings, and the accumulation of indole acetic acid (IAA), GA and zeatin riboside (ZR) were increased, so plant growth was inhibited ( Li et al, 2015 ). Autotoxicity is generally considered to be the main cause of replanting problems and has been documented in various plants ( Ren et al, 2015 ), and effect of autotoxicity seems to relate to the allelochemical concentration, as one study showed that seed germination and the initial growth biomass were inversely correlated with the concentration of the water extract of leaves and roots of plants ( Favaretto, Scheffer-Basso & Perez, 2017 ). Deng et al (2017) discovered that the root exudates of tobacco inhibited its germination and growth of tobacco, and found the dioctyl phthalate and diisooctyl phthalate were the main autotoxic substances exuded by roots.…”
Section: Introductionmentioning
confidence: 99%